Diabetes-induced microvascular complications at the level of the spinal cord: a contributing factor in diabetic neuropathic pain - Ved, Nikita; Da Vitoria Lobo, M.E.; Bestall, Samuel M.; Vidueira, C.L.; Beazley-Long, Nicholas; Ballmer-Hofer, Kurt; Hirashima, Masanori; Bates, David O.; Donaldson, Lucy F.; Hulse, Richard P. (Wiley, 2018)
Abnormalities of neurovascular interactions within the central nervous system of diabetic patients is associated with the onset of many neurological disease states. However, to date, the link between the neurovascular network within the spinal cord and regulation of nociception has not been investigated despite neuropathic pain being common in diabetes. We hypothesised that hyperglycaemia-induced endothelial degeneration in the spinal cord, due to suppression of VEGF-A/VEGFR2 signalling, induces diabetic neuropathic pain. Nociceptive pain behaviour was investigated in a chemically induced model of type 1 diabetes (streptozotocin induced, insulin supplemented; either vehicle or VEGF-A165b treated) and an inducible endothelial knockdown of VEGFR2 (tamoxifen induced). Diabetic animals developed mechanical allodynia and heat hyperalgesia. This was associated with a reduction in the number of blood vessels and reduction in Evans blue extravasation in the lumbar spinal cord of diabetic animals versus age-matched controls. Endothelial markers occludin, CD31 and VE-cadherin were downregulated in the spinal cord of the diabetic group versus controls, as well as a concurrent reduction of VEGF-A165b expression. In diabetic animals, VEGF-A165b treatment (biweekly intraperitoneal, 20ng/g) restored normal Evans blue extravasation and prevented vascular degeneration, diabetes-induced central neuron activation and neuropathic pain. Inducible knockdown of VEGFR2 (tamoxifen treated Tie2CreERT2-vegfr2flfl mice) led to a reduction in blood vessel network volume in the lumbar spinal cord and development of heat hyperalgesia. These findings indicate that hyperglycaemia leads to a reduction in the VEGF-A/VEGFR2 signalling cascade resulting in endothelial dysfunction in the spinal cord, which could be an undiscovered contributing factor to diabetic neuropathic pain.